VD_FINDINFO AI 262/08 - 258/2011 vom 17. Mai 2011 - VD Tribunal cantonal (2011)
RESTITUTIONEN GÉNÉRAL, DEGRÉ DE L'INVALIDITÉ, AGGRAVATION DE L'ATTEINTE À LA SANTÉ, RÉVISIONDÉCISION | 17 LPGA, 25 LPGA, 31 al. 1 LPGA, 2 OPGA, 3 OPGA, 4 al. 2 OPGA, 77 RAI, 87 al. 2 RAI, 88a al. 1 RAI, 88bis al. 2 RAI